Science education in Malaysia: Challenges in the 21stcentury - Sumintono, B. (2015)
This article analyses the development of science education in the Malaysian schools’ context. Several big changes have shiftedthe direction of science teaching to Malaysian students over the last fifty years. It started with curriculum reforms adopted by western countriesin the 1960s and 1970s. The introduction of a new curriculum with an underlying ‘child-centred’ philosophy was developed and implemented in the 1980s. The importance of information technology and English as medium of instructionwere characteristic in the late 1900s and 2000s. The impact of international study’s such as TIMSS and PISA paved a new direction for science education.Dynamics ofscience education in Malaysia shows interesting developments that informs us how the education system has adaptedto challenges and trends.